Allicin prevents the formation of Proteus-induced urinary crystals and the blockage of catheter in a bladder model in vitro. (July 2019) - Imani Rad, Hamed; Peeri, Hadi; Amani, Mojtaba; Mohammadnia, Alireza; Ogunniyi, Abiodun David; Khazandi, Manouchehr; Venter, Henrietta; Arzanlou, Mohsen
Abstract: Stone formation and catheter blockage are major complications of Proteus UTIs. In this study, we investigated the ability of allicin to inhibit P. mirabilis -induced struvite crystallization and catheter blockage using a synthetic bladder model. Struvite crystallization inhibition study was carried out using P. mirabilis lysate as urease enzyme source in synthetic urine (SU). Struvite productions were monitored by phase contrast light microscopy and measurements of pH, Mg 2+ and Ca 2+ precipitation and turbidity. A catheter blockage study was performed in a synthetic bladder model mimicking natural UTI in the presence of allicin at sub-MIC concentrations (MIC = 64 μg/ml). The results of crystallization study showed that allicin inhibited pH rise and consequently turbidity and precipitation of ions in a dose-dependent manner. The results of catheter blockage study showed that allicin at sub-MIC concentrations (2, 4, 8 μg/ml) significantly increased the time for catheter blockage to occur to 61, 74 and 92 h respectively compared to allicin-free control (48 h). In a similar way, the results showed that allicin delayed the increase of SU pH level in bladder model in a dose-dependent manner compared to allicin-free control. The results also showed that following the increase of allicin concentration, Mg 2+ and Ca 2+ deposition in catheters were much lower compared to allicin-free control, further confirmed by direct observation of the catheters' eyehole and cross sections. We conclude that allicin prevents the formation of Proteus -induced urinary crystals and the blockage of catheters by delaying pH increase and lowering Mg 2+ and Ca 2+ deposition in a dose-dependent manner. Highlights: Stone formation and catheter blockage are frequent complications of Proteus spp UTIs. . Allicin inhibits P. mirabilis -induced pH rise of synthetic urine and hence precipitation of ions and crystals formation Allicin. prevents pH rise of P. mirabilis -infected synthetic urine and delays catheter blockage using a synthetic bladder. Allicin can be considered as a potential candidate to prevent Proteus -induced urinary crystals development and hence catheters blockage.